Study of single layer microwave absorber based on rice husk Ash/CNTs composites - Y.S. Lee; F.H. Wee; K.Y. You; Z. Liyana; C.Y Lee; Mas Elyna Azol; M.H. Ramli; H.S. Gan; M.S. Shakhirul; Nurulbariah Idris; E.M. Cheng (Institute of Advanced Engineering and Science, 2019)
This paper presents the study of microwave absorption single layer microwave absorber based on rice husk ash (RHA) with additional carbon nanotubes (CNTs) filler loading into the composites. The relative permittivity of RHA and CNTs composites (RHA/CNTs) were measured by using Agilent high temperature probe and 85070E software. The CST-MWS software is used to design and evaluate the microwave absorption of RHA and RHA/CNTs with metal backed plate. The microwave absorption of simulated and measured results is compared. The RHA microwave absorber only absorbed maximum, -8 dB at 10.8 GHz of the incident electromagnetic radiation and the RHA/CNTs absorbed less than -15 dB with wider bandwidth over 10.8 GHz to 12.8 GHz compare with RHA composites single layer microwave absorber. The results indicated that the RHA/CNTs composites have enhanced the microwave absorption of RHA composites.